Sensitivity of photosystem 2 of Antarctic lichens to high irradiance stress: Fluorometric study of fruticose (Usnea antarctica) and foliose (Umbilicaria decussata) species - Barták, M.; Vráblíková, H.; Hájek, J.
Two lichen species collected in maritime Antarctica (King George Island) were exposed under laboratory conditions to excess irradiance to evaluate the response of photosystem 2 (PS2). The response was measured on fully hydrated lichen thalli at 5 °C by means of a modulated fluorometer using chlorophyll (Chl) fluorescence induction curve supplemented with analysis of quenching mechanisms. Chl fluorescence parameters [i.e. ratio of variable to maximum Chl fluorescence (FV/FM), quantum yield of PS2 photochemical reactions (Φ2), quenching coefficients] were evaluated before and several times after exposition to high irradiance in order to characterise the extent of photoinhibition, fast and slow phase of recovery. Strong irradiance (2 000 μmol m-2 s-1) caused high degree of photoinhibition, particularly higher in fruticose (Usnea antarctica) than in foliose (Umbilicaria decussata) lichen species. Fast phase of recovery from photoinhibition, corresponding to regulatory mechanisms of PS2, was more apparent in U. decussata and Φ2 than in U. antarctica and FV/FM and Φ2 within 40 min after photoinhibitory treatment. It was followed by a slow phase lasting several hours, corresponding to repair and re-synthesis processes. After photoinhibitory treatment, recovery of non-photochemical quenching (NPQ) was faster and more pronounced in U. decussata than in U. antarctica. Significant differences were found between the two species in the rate of recovery in fast-(qE) and slow-recovering (qT+I) component of NPQ. M. Barták, H. Vráblíková, J. Hájek.